Examining the Integration of Legal and Shariah Principles In the London Metal Exchange - A. Alotaibi, Hajed (Journal of Ecohumanism, 2024)
Purpose: The Islamic banking system is recognized for its role in promoting the equal distribution of resources and its emphasis on risk management. This research paper explores the rulings of the London Metal Exchange (LME) within the framework of Islamic law. The main objective is to investigate the involvement and impact of Islamic banking in LME contracts. Methods: The study utilizes both primary data, obtained through interviews with Islamic banks and LME management, and secondary data from previous research. Results: The findings highlight the significant role of Islamic banks in facilitating LME contracts, with Murabaha, Tawarruq, Istisna, Salam, and Kafala identified as the most commonly used instruments in the GCC regions. However, Islamic banks also face challenges, including criticism from Muslim scholars regarding certain practices. Conclusion: Despite these challenges, there are several opportunities for Islamic banks to contribute to the further development of the Islamic financial system. By addressing concerns, increasing awareness, and adhering to Islamic principles, Islamic banks can play a pivotal role in shaping the future of the financial industry.